Thiadiazole Cyclic Derivatives from Aldamine Compounds (Preparation, Characterization, Thermal Stability) - Athraa Sahib Alrammahi (Journal of Global Pharma Technology, 2018)
Seven heterocyclic derivatives were synthesized by using Azotation reaction ,followed by coupling reaction with phenol derivative , the resulting compound cyclized with thiosemicarbazide to yield thiadiazole derivatives which reacted with carbonyl compound ( benzaldehyde) with drops of glacial acetic acid to produce imine compound followed by breaking of imine bond (CH=N) to react with ( succinic anhydride , chloroaceto chloride , glycine , ortho mercapto benzoic acid ) to yield cyclic derivatives from Aldamine-thiadiazole derivatives. Thiadizole-aldamine derivatives were characterized by chemical techniques such as (1H NMR , IR and Mass- spectra , Thermal Stability).Keywords: Therm, Technic, Stable.